SHALAWATAN CELEBRATION IN PROBOLINGGO COMMUNITY CULTURAL FRAME: Study of Symbolic Interactionism - Ahmad Fauzi (IAIN Ponorogo, 2019)
Abstract: Sociologically, the celebration of shalawatan in essence cannot be separated from social culture in society as part of local wisdom. Therefore, various forms of shalawatan activities are realized in various ways, in accordance with the understanding in expressing their religion, -shalawatan- with the aim of invoking blessing and salvation. Specifically, this research is more focused on; the meaning of the celebration of shalawatan and symbolizing the values of shalawatan. Meanwhile, to answer this problem, researcher use the theory of symbolic interactionism, through the dialectic between (mind, self and society). This study uses a phenomenological approach to the type of qualitative research and generally produces several findings; a) the meaning of shalawatan celebration gives birth to various social symbols which are verbal and nonverbal. The construction of the intended symbolism is interpreted as part of the formation of individual social behavior in the midst of society, individual behavior is determined by meaning as a result of interactions in shalawatan activities. b) symbolization of shalawatan construction is an individual product by observing the surrounding social conditions which can then underlie the formation of individual social behavior, both through; (body language), local language and physical movement. Therefore, the entire life of an individual cannot be separated from the use of symbols as an illustration to convey certain messages to the public. Practically, the symbol of the shalawatan celebration gives birth to several aspects of value, including; appointment as part of the process of character building; social harmonization; soul cleansing (tazkiyyat al-nafs); as a moral fortress in maintaining the integrity of the NKRI; so that its existence really becomes rahmat li al-'a>lami>n.الملخص: من الناحية الاجتماعية ، لا يمكن فصل الاحتفال صلاواتان في اختلافا عن الثقافة الاجتماعية في المجتمع كجزء من الحكمة المحلية. لذلك تتحقق أشكال مختلفة من أنشطة صلاواتان بطرق مختلفة ، وفقًا لفهم التعبير عن دينهم - صلاواتان - بهدف التذرع بالبركة والخلاص. على وجه التحديد هذا البحث هو أكثر تركيزا على. معنى احتفال صلااواتان ورمز قيمة صلاواتان. أثناء الإجابة عن هذه المشكلة ، يستخدم الباحث نظرية التفاعل الرمزي ، من خلال الجدلية بين (العقل والنفس والمجتمع). يستخدم هذه الدراسة نهجًا ظاهريًا لنوع البحث النوعي وتنتج عمومًا العديد من النتائج ؛ أ) معنى الاحتفال بصلاوات يلد الرموز الاجتماعية المختلفة التي هي لفظية وغير لفظية. يتم تفسير بناء الرمزية المذكورة كجزء من تكوين السلوك الاجتماعي الفردي في وسط المجتمع ، ويتم تحديد السلوك الفردي بالمعنى نتيجة للتفاعل في أنشطة صلاواتان. السلوك الاجتماعي الفردي ، من خلال (لغة الجسد) ، واللغة المحلية والحركة البدنية. لذلك ، لا يمكن فصل حياة الفرد بالكامل عن استخدام الرموز كتوضيح لنقل رسائل معينة إلى الجمهور. في التطبيق العملي ، تلد رموز الاحتفال بالصلاة جوانب عديدة من القيمة ، بما في ذلك ؛ التعيين كجزء من عملية بناء الشخصية ؛ اشتراكية متناغمة تطهير الروح (تزكية النفس) ؛ كقلعة أخلاقية في الحفاظ على سلامة NKRI ؛ بحيث يصبح وجودها حقا رحمة للعآلمين.Abstrak: Secara sosiologis, perayaan shalawatan pada hakikatnya tidak dapat dipisahkan dari sosial budaya di masyarakat sebagai bagian dari kearifan lokal. Karena itu, berbagai bentuk kegiatan shalawatan diwujudkan melalui berbagai macam cara sesuai dengan pemahaman dalam mengekspresikan keagamaannya –shalawatan– dengan tujuan untuk memohon keberkahan dan keselamatan. Secara spesifik, penelitian ini lebih difokuskan pada; makna perayaan shalawatan dan simbolisasi nilai-nilai shalawatan. Sementara, untuk menjawab persoalan tersebut, peneliti menggunakan interaksionisme simbolik, melalui dialektika antara (mind, self and society). Penelitian ini menggunakan pendekatan fenomenologis dengan jenis penelitian kualitatif dan secara umum melahirkan beberapa temuan; a) makna perayaan shalawatan melahirkan berbagai simbol sosial, yaitu bersifat verbal dan nonverbal. Konstruksi atas simbolisasi dimaksud, ditafsirkan sebagai bagian dari terbentuknya perilaku sosial individu di tengah-tengah masyarakat, perilaku individu ditentukan oleh makna sebagai akibat dari interaksi dalam kegiatan shalawatan. b) konstruksi simbolisasi shalawatan merupakan produk individu dengan memperhatikan kondisi sosial di sekelilingnya yang kemudian dapat mendasari terbentuknya perilaku sosial individu, baik melalui; (body language), bahasa lokal maupun gerak fisik. Karena itu, seluruh kehidupan individu tidak dapat dilepaskan dari penggunaan simbol sebagai gambaran untuk menyampaikan pesan tertentu kepada publik. Secara praksis, simbol-simbol perayaan shalawatan melahirkan beberapa aspek nilai, antara lain; shalawatan sebagai bagian dari proses pembentukan karakter; harmonisasi sosial; pembersian jiwa; benteng moral dalam menjaga keutuhan NKRI; sehingga keberadaanya benar-benar menjadi rahmat li al-'a>lami>n.